Digital Transformation and Legal Awareness: An Empirical Study on Citizen Engagement through Legal Reporting Applications in Urban Areas - Sosal, Baron; Agustiansyah, Budi; Kinaya, Neria (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
Digital transformation has significantly reshaped how urban citizens interact with legal systems, particularly through mobile applications such as LAPOR!, Qlue, and JAKI. While these platforms are intended to promote legal awareness and civic participation, their effectiveness remains unclear due to the gap between technological adoption and legal literacy. This study aims to examine the extent of citizen engagement in legal reporting via digital platforms and assess how digital transformation influences legal awareness in urban settings. Employing a quantitative approach, the study used an online survey method with 300 respondents from Jakarta, Bandung, and Surabaya—cities known for implementing legal reporting applications. The data were analyzed using descriptive and inferential statistics, including chi-square tests and logistic regression. The results indicate a relatively high usage rate of legal reporting apps; however, users' understanding of legal procedures remains moderate. Statistical analysis revealed that frequency of app usage and trust in legal institutions significantly affect legal awareness. Nevertheless, technological engagement alone does not automatically translate into improved legal understanding. The study highlights the need for integrated digital legal education within reporting applications and emphasizes institutional transparency as a driver of citizen trust and participation. This research contributes to the e-governance literature by proposing legal awareness as a critical normative variable, offering theoretical insights and practical recommendations for building more inclusive and participatory digital legal systems.